Banking Sector Profitability During The Covid-19 Pandemic - Krensia Isidora Wea Wea; Ni Luh Anik Puspa Ningsih; Ida Ayu Surasmi (Jurnal Ekonomi dan Bisnis Jagaditha, 2023)
Covid-19 has a crucial impact on various industrial sectors in Indonesia. One of the sectors affected is banking. Companies are guided to maintain maximum performance. Profitability is one indicator that reflects the company's performance. Profitability is the company's ability to earn profits during a certain period. In achieving maximum profitability, banks need to optimize the internal company that plays a role in achieving profitability. This study aims to examine the effect of Non Performing Loans (NPL), Loan to Deposit Ratio (LDR) on Return on Assets (ROA) through Net Interest Margin (NIM). The population of this research is the banking industry companies in Indonesia. The population in this study are 29 banks listed on the IDX. The method used in this study is a purposive sampling method, a sample of 24 banks listed on the Indonesia Stock Exchange was obtained. The data analysis technique used is path analysis. The findings of this study are that LDR has a significant negative effect on NIM, but a significant positive effect on ROA. NPL has a significant negative effect on NIM, and a significant negative effect on ROA. NIM was found to be able to partially mediate the effect of LDR on ROA. NIM mediates some of the NPL against ROA. The predictive ability of these three variables on ROA in this study was 22.5%, while the remaining 77.5% was influenced by other factors which were not included in the research model.